Tobacco Production and Trade in Macedonia ' the Legal Framework and Policy in Light of Access to the EU and the Global Markets - Zdraveva, Neda (University of Belgrade, Faculty of Law, 2018)
In the paper the author analyses the national legislation related to the production (manufacture) and trade (sale) of tobacco and tobacco products. The aim of the research is to establish the level of the harmonization of the national legislation to the relevant EU and international instruments in the field. The paper examines the specific rules for agricultural production of tobacco and its treatment as controlled substance, from the aspect of administrative perquisites and contractual relations that emerge. The key issue of interest is the regulation of the standards and conditions for releasing the tobacco and tobacco products on the markets, with emphasis on the labelling requirements. Beside these issues, the author also deals with the other policy instruments related to the tobacco control. It is concluded that the current legislation is not aligned with the applicable EU law in this field and that further legislative activities are needed. The author stresses that political will be needed not only to enact new legislation but also to effectively and efficiently enforce it.
Keywords: - Tobacco products. - Tobacco Products Directive. - Framework Convention on Tobacco Control.